Arnold Snyder's "In search of the Swiss Brethren": a response - Neufeld, David Yoder ca. 20./21. Jh. (The Mennonite quarterly review, 2016)
The article discusses research on the history of Anabaptism dealing with the processes of confessional faith among Anabaptists, ethical biblicism, and early Modern European historiography.